Organic-inorganic composite spongy porous diaphragm as well as preparation method and application thereof
By mixing polyarylether polymer materials, pore-generating agents and metal oxide nanoparticles and phase conversion, an organic-inorganic composite sponge-like porous membrane was prepared, which solved the pore connectivity and pore size control of the membrane in the prior art. The problem of insufficient has significantly improved the efficiency and energy efficiency of hydrogen production by electrolyzing water.
Patent Information
- Application Number
- CN202411519953.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing alkaline water electrolysis technology, the pore connectivity and pore size control of the diaphragm are insufficient, resulting in high resistance and increased energy consumption, making it difficult to meet the needs of large-scale hydrogen production applications.
Polyarylether polymer materials, porogens, metal oxide nanoparticles and organic solvents are used to mix and defoam to form a cast film liquid. Through pre-phase conversion, a sponge-like porous structure is formed in humid air, and then in the extraction agent Phase conversion is carried out, and the polyarylether polymer material is enriched to form a continuous phase and cured to obtain an organic-inorganic composite sponge-like porous separator.
It significantly improves the hydrophilic performance and pore connectivity of the diaphragm, reduces resistance, improves the current density and energy efficiency of hydrogen production by alkaline electrolyzing water, and reduces the cost of equipment and power consumption.
Smart Images

Figure CN119236697A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diaphragms, and in particular relates to an organic-inorganic composite sponge-like porous diaphragm and a preparation method and application thereof. Background Art
[0002] Hydrogen energy, with its zero pollution, high calorific value, easy storage and wide application fields, is gradually becoming an important part of the future energy system. Water electrolysis technology, especially the use of renewable energy and fluctuating surplus electricity to produce hydrogen, is regarded as the most ideal and environmentally friendly way to produce hydrogen. However, the current global hydrogen production from water electrolysis accounts for only 4%, and the high cost, especially the power consumption and electrolyzer cost, has become a key factor restricting its large-scale application. Alkaline water electrolysis technology has attracted much attention due to its low cost, long life, rich material sources and suitability for large-scale hydrogen production. However, in the large-scale hydrogen production application scenario, improving the current density and energy efficiency of alkaline water electrolysis technology, and then reducing the equipment and power consumption costs, has become a technical problem that needs to be solved urgently. Among them, the diaphragm is a key component of the electrolyzer, and its performance has a crucial impact on the power consumption and hydrogen purity of the electrolyzer.
[0003] In the early alkaline water electrolysis hydrogen production technology, asbestos diaphragms were eliminated from the market due to health and safety issues. Polyphenylene sulfide (PPS) diaphragms, as a replacement, have obvious shortcomings in performance, especially in terms of hydrophilicity and resistance. This not only increases energy consumption, but also reduces the safety of the system.
[0004] At the same time, the existing technology uses the organic-inorganic composite finger-shaped porous diaphragm prepared by directly phase-inverting the liquid membrane, which has the problem of too large pore size and disconnected pore structure. This problem easily leads to the appearance of dead zones, which in turn hinders the effective conduction of ions, increases impedance, and is difficult to meet the needs of practical applications. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides an organic-inorganic composite sponge-like porous diaphragm and a preparation method and application thereof. The present invention mixes polyarylether polymer materials, porogens, metal oxide nanoparticles and organic solvents and then defoams to obtain a casting liquid, and after being scraped on a glass plate to form a liquid film, a pre-phase conversion is carried out in a humid air atmosphere to induce the liquid film to form a through sponge-like porous structure, and then a phase conversion is carried out in an extractant, and the polyarylether polymer materials are enriched to form a continuous phase and solidified to obtain an organic-inorganic composite sponge-like porous diaphragm. The present invention combines pre-phase conversion with phase conversion to obtain an organic-inorganic composite sponge-like porous diaphragm, which not only overcomes the deficiencies of the existing finger-like porous diaphragm in terms of pore connectivity and pore size control, but also significantly improves the hydrophilicity of the diaphragm, while greatly reducing the resistance.
[0006] In order to achieve the above purpose, the technical solution adopted in this application is:
[0007] The first object of the present invention is to provide a method for preparing an organic-inorganic composite sponge-like porous diaphragm, comprising the following steps:
[0008] S1. Mix a polyarylether polymer material, a porogen, metal oxide nanoparticles and an organic solvent, and then perform a defoaming treatment to obtain a casting solution, and prepare the casting solution into a liquid film; in the casting solution, the mass percentage of the polyarylether polymer material is 5% to 20%, the mass percentage of the porogen is 0.5% to 5%, the mass percentage of the metal oxide nanoparticles is 0.5% to 10%, and the organic solvent is supplemented to 100%; wherein, if the amount of the polyarylether polymer material is too little, the casting solution is too thin and a thicker liquid film cannot be obtained, and if the amount of the polyarylether polymer material is too much, the casting solution is too viscous, the phase conversion process is slow and incomplete, and an organic-inorganic composite sponge-like porous diaphragm with a continuous membrane pore structure cannot be obtained; the amount of the porogen affects the size of the membrane pores; the amount of the metal oxide nanoparticles affects the hydrophilicity of the organic-inorganic composite sponge-like porous diaphragm.
[0009] The polyarylether polymer material is selected from polyarylether polymers or sulfonated derivatives of polyarylether polymers; the defoaming treatment is to prevent bubbles from causing defects in the organic-inorganic composite sponge-like porous diaphragm.
[0010] S2. Place the casting liquid on a glass plate and apply it by scraping to obtain a liquid film.
[0011] S3. The liquid film is placed in a humid air atmosphere for pre-phase conversion. During the pre-phase conversion, water vapor in the humid air partially penetrates into the liquid film and undergoes a preliminary exchange with the organic solvent in the liquid film, thereby inducing the formation of a through sponge-like porous structure inside the liquid film, thereby obtaining a sponge-like porous liquid film.
[0012] S4. The sponge-like porous liquid membrane is then placed in an extractant for phase transformation. During the phase transformation, the membrane pores of the sponge-like porous liquid membrane gradually condense. At the same time, the polyarylether polymer material is enriched to form a continuous phase and solidified into a film, thereby obtaining an organic-inorganic composite sponge-like porous diaphragm.
[0013] Preferably, the organic-inorganic composite sponge-like porous membrane is placed in the extractant to remove the residual organic solvent, promote the complete phase conversion process, and reduce the harm of the organic solvent to human health.
[0014] Preferably, the thickness of the liquid film is 100 μm to 1000 μm; wherein, if the thickness of the liquid film is less than 100 μm, the strength of the organic-inorganic composite sponge-like porous diaphragm is poor; and if the thickness of the liquid film is too high, the impedance of the organic-inorganic composite sponge-like porous diaphragm is too large.
[0015] Preferably, the conditions for the pre-phase transformation are: exposing the liquid film to a humid air atmosphere with a relative humidity of 30% to 80% for 1 minute to 30 minutes; wherein, if the relative humidity is too low, the liquid film cannot undergo pre-phase transformation; conversely, if the relative humidity is too high, the pre-phase transformation speed of the liquid film will be too fast, and the effect will be almost the same as directly immersing it in water for phase transformation, and it will not be possible to effectively induce the formation of a sponge-like porous structure; and the longer the exposure time, the more complete the pre-phase transformation, and the more conducive it is to the formation of a through sponge-like porous structure.
[0016] Preferably, the phase transformation conditions are: placing the sponge-like porous liquid membrane in an extractant, soaking it at 0°C to 80°C for 2h to 48h; wherein, if the temperature is too high, the phase transformation process will be accelerated, resulting in the membrane pore structure of the organic-inorganic composite sponge-like porous membrane being too loose and the pore size being too large, thereby weakening the selective permeability of the organic-inorganic composite sponge-like porous membrane. On the contrary, if the temperature is too low, the phase transformation rate will be slowed down, resulting in the membrane pores of the organic-inorganic composite sponge-like porous membrane being too dense and the pore size being too small, affecting the transmission efficiency and flux of the substance. Too long an immersion time will excessively promote the phase transformation, causing the overdevelopment of the membrane pore structure, affecting the performance stability of the organic-inorganic composite sponge-like porous membrane; and if the immersion time is too short, the phase transformation process will be insufficient, the membrane pores of the organic-inorganic composite sponge-like porous membrane will not be sufficiently developed, resulting in a decrease in the separation efficiency and durability of the organic-inorganic composite sponge-like porous membrane.
[0017] Preferably, the polyarylether polymer material is selected from polyethersulfone, sulfonated polyethersulfone, polysulfone, sulfonated polysulfone, polyetheretherketone or sulfonated polyetheretherketone.
[0018] Preferably, the organic solvent is selected from N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide or N,N-dimethylformamide.
[0019] Preferably, the porogen is selected from di-n-butyl phthalate, polyethylene glycol or polyvinyl pyrrolidone.
[0020] Preferably, the metal oxide nanoparticles are selected from ZrO 2 、TiO 2 、Al 2 O 3 、SiO 2 、CeO 2 、MnO 2 or Fe 3 O 4 At least one of .
[0021] Preferably, the particle size of the metal oxide nanoparticles is 5 nm to 500 nm. The particle size of the metal oxide nanoparticles will affect the pore size and performance of the organic-inorganic composite porous diaphragm.
[0022] The second object of the present invention is to provide an organic-inorganic composite sponge-like porous diaphragm prepared by the above preparation method.
[0023] The third object of the present invention is to provide the use of the organic-inorganic composite sponge-like porous diaphragm prepared above in the preparation of an alkaline water electrolysis diaphragm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention provides a method for preparing an organic-inorganic composite sponge-like porous diaphragm, wherein a polyarylether polymer material, a porogen, metal oxide nanoparticles and an organic solvent are mixed and defoamed to obtain a casting liquid; the casting liquid is placed on a glass plate for scraping to obtain a liquid film; the liquid film is placed in a humid air atmosphere with a relative humidity of 30% to 80% for pre-phase transformation, during which the liquid film is induced to form a through sponge-like porous structure, and then phase transformation is performed in an extractant, during which the membrane pores of the sponge-like porous liquid film are condensed, and at the same time, the polyarylether polymer material is enriched to form a continuous phase and solidified into a film, thereby obtaining an organic-inorganic composite sponge-like porous diaphragm. The preparation method of the present invention not only overcomes the defects of the existing diaphragm in terms of pore connectivity and pore size control, but also significantly improves the hydrophilicity of the diaphragm and greatly reduces the resistance.
[0026] Among them, the porogen regulates the internal pore structure of the organic-inorganic composite sponge-like porous membrane, and the metal oxide nanoparticles are used to improve the hydrophilicity of the organic-inorganic composite sponge-like porous membrane and adjust the pore size; the defoaming treatment is to avoid bubbles causing defects in the organic-inorganic composite sponge-like porous membrane; in the pre-phase transformation process, the water vapor in the humid air atmosphere will partially penetrate into the liquid film, and undergo preliminary exchange with the organic solvent in the liquid membrane, inducing the formation of a preliminary, through-going sponge-like porous structure inside the liquid membrane.
[0027] During the phase transformation process, the extractant and the organic solvent in the sponge-like porous liquid membrane diffuse and exchange rapidly, causing the sponge-like porous liquid membrane system to become thermodynamically unstable, thereby inducing phase separation. During the phase separation process, the polyarylether polymer material is enriched to form a continuous membrane phase, while the organic solvent and the extractant form a dispersed phase. With the further exchange of the organic solvent and the extractant, the pores of the sponge-like porous liquid membrane gradually condense and the interphase flow intensifies, causing the polyarylether polymer material to be enriched and solidified, and finally obtaining an organic-inorganic composite sponge-like porous diaphragm.
[0028] 2. The present invention applies the prepared organic-inorganic composite sponge-like porous diaphragm to the electrolysis of alkaline water. Compared with the diaphragm prepared by the traditional technology, the organic-inorganic composite sponge-like porous diaphragm prepared by the present invention has its internal pores interpenetrating each other, which greatly promotes the full infiltration of alkaline water, thereby giving the organic-inorganic composite sponge-like porous diaphragm extremely low ionic impedance characteristics, making ion transmission smoother. In a 30% mass concentration KOH alkaline water electrolysis system, the organic-inorganic composite sponge-like porous diaphragm significantly reduces the voltage requirement for hydrogen production by alkaline water electrolysis, thereby improving the overall efficiency and effect of hydrogen production by alkaline water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an electron microscope image of the cross section of the organic-inorganic sponge-like porous diaphragm prepared in Example 1.
[0030] Figure 2 This is an electron microscope image of the cross section of the organic-inorganic finger-shaped porous diaphragm prepared in Comparative Example 1.
[0031] Figure 3 Ionic impedance diagrams of the organic-inorganic sponge-like porous membrane prepared in Example 1, the organic-inorganic finger-like porous membrane prepared in Comparative Example 1, the carbon membrane, the carbon energy membrane, the carbon harmonic membrane, and the Cobetter membrane.
[0032] Figure 4 The water contact angle results of the organic-inorganic sponge-like porous membrane prepared in Example 1, the organic-inorganic finger-like porous membrane prepared in Comparative Example 1, the carbon membrane, the carbon energy membrane, the carbon harmonic membrane and the Cobetter membrane. DETAILED DESCRIPTION
[0033] The technical scheme of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods. Among them: commercial membrane 1 is a carbon membrane, commercial membrane 2 is a carbon energy membrane, commercial membrane 3 is a carbon harmonic membrane, and commercial membrane 4 is a Cobetter membrane; dimethyl sulfoxide, denoted as DMSO.
[0034] In the prior art, although alkaline water electrolysis technology has shown great potential in the field of hydrogen production, the performance bottleneck of diaphragm materials has seriously restricted the further optimization of its current density, energy efficiency and overall cost. Traditional diaphragm materials such as asbestos have been eliminated, and polyphenylene sulfide diaphragms perform poorly in terms of hydrophilicity and resistance characteristics. At the same time, the prior art uses an organic-inorganic composite finger-shaped porous diaphragm prepared by directly phase-inverting the liquid membrane, which has the problem of too large pore size and disconnected pore structure. This problem easily leads to the appearance of dead zones, which in turn hinders the effective conduction of ions, increases impedance, and is difficult to meet the needs of practical applications.
[0035] In view of the problems existing in the prior art, the present invention provides a method for preparing an organic-inorganic composite sponge-like porous diaphragm, comprising the following steps: mixing a polyarylether polymer material, a porogen, metal oxide nanoparticles and an organic solvent, and then performing a defoaming treatment to obtain a casting liquid, and preparing the casting liquid into a liquid film; in the casting liquid, the mass percentage of the polyarylether polymer material is 5% to 20%, the mass percentage of the porogen is 0.5% to 5%, the mass percentage of the metal oxide nanoparticles is 0.5% to 10%, and the organic solvent is supplemented to 100%; the polyarylether polymer material is 0.5% to 10%, and the mass percentage of the metal oxide nanoparticles is 0.5% to 10%. The material is selected from polyarylether polymers or sulfonated derivatives of polyarylether polymers; the liquid membrane is placed in a humid air atmosphere for pre-phase transformation. During the pre-phase transformation, water vapor in the humid air partially penetrates into the liquid membrane and undergoes preliminary exchange with the organic solvent in the liquid membrane, inducing the formation of a through sponge-like porous structure inside the liquid membrane to obtain a sponge-like porous liquid membrane; the sponge-like porous liquid membrane is then placed in an extractant for phase transformation. During the phase transformation, the membrane pores of the sponge-like porous liquid membrane condense, and at the same time, the polyarylether polymer material is enriched to form a continuous phase and solidified into a film, thereby obtaining an organic-inorganic composite sponge-like porous diaphragm.
[0036] The non-solvent induced phase separation method, also known as the wet method, is to dissolve the polymer polyarylether polymer material in an organic solvent to form a uniform casting liquid. Subsequently, an extractant that is highly miscible with the organic solvent is slowly added to promote the precipitation of the organic solvent. The organic solvent and the extractant will diffuse and exchange at the interface between the sponge-like porous liquid membrane and the extractant until a sufficient state of exchange is reached. At this time, the sponge-like porous liquid membrane becomes a thermodynamically unstable state, inducing a phase separation phenomenon and then forming a two-phase structure in which the polyarylether polymer material is a continuous phase and the solvent is a dispersed phase. At the phase interface of the sponge-like porous liquid membrane, the mass transfer of the organic solvent and the extractant (i.e., the mass transfer process) drives the phase transformation. As the system separates phases, the organic solvent and the extractant are further exchanged, resulting in the condensation of the sponge-like porous liquid membrane pores, the interphase flow of the continuous phase and the dispersed phase, and the enrichment of the polyarylether polymer material to form a continuous phase and solidify into a film. The organic solvent is then removed to obtain a polymer material with a porous structure.
[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0038] Example 1
[0039] A method for preparing an organic-inorganic composite sponge-like porous diaphragm comprises the following steps:
[0040] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0041] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0042] S3. After exposure to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0043] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0044] Example 2
[0045] A method for preparing an organic-inorganic composite sponge-like porous separator is the same as the preparation steps of Example 1, except that the relative humidity of the air atmosphere in S3 is replaced from 60% to 30%, and the soaking time in deionized water at 80° C. is replaced from 24 h to 48 h, comprising the following steps:
[0046] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0047] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0048] S3. After exposure to an air atmosphere with a relative humidity of 30% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0049] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 48 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0050] Example 3
[0051] A method for preparing an organic-inorganic composite sponge-like porous separator is the same as the preparation steps of Example 1, except that the relative humidity of the air atmosphere in S3 is replaced from 60% to 80%, and the soaking time in deionized water at 80° C. is replaced from 24 h to 2 h, comprising the following steps:
[0052] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0053] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0054] S3. After being exposed to an air atmosphere with a relative humidity of 80% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0055] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 2 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0056] Example 4
[0057] A method for preparing an organic-inorganic composite sponge-like porous separator is the same as the preparation steps of Example 1, except that the exposure time in S3 is replaced from 10 min to 30 min, comprising the following steps:
[0058] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0059] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0060] S3. After exposure to an air atmosphere with a relative humidity of 60% for 30 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0061] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0062] Example 5
[0063] A method for preparing an organic-inorganic composite sponge-like porous separator is the same as the preparation steps of Example 1, except that the exposure time in S3 is replaced from 10 min to 1 min, comprising the following steps:
[0064] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0065] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0066] S3. After exposure to an air atmosphere with a relative humidity of 60% for 1 min, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0067] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0068] Example 6
[0069] A method for preparing an organic-inorganic composite sponge-like porous diaphragm, which has the same preparation steps as those of Example 1, except that the thickness of the liquid film in S2 is replaced from 200 μm to 100 μm, comprises the following steps:
[0070] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0071] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 100 μm liquid film.
[0072] S3. After exposure to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0073] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 2 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0074] Example 7
[0075] A method for preparing an organic-inorganic composite sponge-like porous diaphragm, which has the same preparation steps as those of Example 1, except that the thickness of the liquid film in S2 is replaced from 200 μm to 500 μm, comprises the following steps:
[0076] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0077] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 500 μm liquid film.
[0078] S3. After exposing the liquid film to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0079] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0080] Example 8
[0081] A method for preparing an organic-inorganic composite sponge-like porous diaphragm, which has the same preparation steps as those of Example 1, except that the thickness of the liquid film in S2 is replaced from 200 μm to 1000 μm, comprises the following steps:
[0082] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0083] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 1000 μm liquid film.
[0084] S3. After exposing the liquid film to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0085] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0086] Example 9
[0087] A method for preparing an organic-inorganic composite sponge-like porous diaphragm is the same as the preparation steps of Example 1, except that 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone, and 5wt% ZrO in S1 are added. 2 Replaced with 5wt% polyethersulfone, 0.5wt% polyvinylpyrrolidone, 0.5wt% ZrO 2 , including the following steps:
[0088] S1, 5wt% polyethersulfone, 0.5wt% polyvinylpyrrolidone and 0.5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0089] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0090] S3. After exposing the liquid film to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0091] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0092] Example 10
[0093] A method for preparing an organic-inorganic composite sponge-like porous diaphragm is the same as the preparation steps of Example 1, except that 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone, and 5wt% ZrO in S1 are added. 2 Replaced with 20wt% polyethersulfone, 5wt% polyvinylpyrrolidone, 10wt% ZrO 2 , including the following steps:
[0094] S1, 20wt% polyethersulfone, 5wt% polyvinylpyrrolidone and 10wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0095] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0096] S3. After exposing the liquid film to an air atmosphere with a relative humidity of 60% for 10 minutes, a pre-phase conversion is performed to obtain a sponge-like porous liquid film.
[0097] S4. Put the sponge-like porous liquid membrane into deionized water. After the sponge-like porous liquid membrane falls off from the glass plate, soak it in deionized water at 80° C. for 24 hours. Use deionized water to completely wash away the residual solvent to obtain an organic-inorganic composite sponge-like porous diaphragm.
[0098] Comparative Example 1
[0099] A method for preparing an organic-inorganic composite finger-shaped porous diaphragm is the same as the preparation steps of Example 1, except that in step S2, after being scraped into a 200 μm liquid film, no exposure treatment is performed, and deionized water coagulation is directly performed, comprising the following steps:
[0100] S1, 15wt% polyethersulfone, 2wt% polyvinylpyrrolidone and 5wt% ZrO with a particle size of 50nm 2 The solution was dissolved in DMSO, stirred at 60°C for 12 h until completely dissolved, and then ultrasonically defoamed to obtain a casting solution.
[0101] S2. Pour the casting liquid onto a clean glass plate and scrape it to form a 200 μm liquid film.
[0102] S3. The liquid film is quickly placed in deionized water. After the liquid film falls off the glass plate, it is immersed in deionized water at 80° C. for 24 hours to completely wash away the residual solvent, thereby obtaining an organic-inorganic composite finger-shaped porous diaphragm.
[0103] a. The test method is as follows:
[0104] Morphology observation: Observation was performed using a JEOL scanning electron microscope (model JSM-6360LV) with an accelerating voltage of 20 kV.
[0105] Electrochemical impedance spectroscopy test: The test was carried out using a Swiss Metrohm AutoLab electrochemical workstation (model PGSTAT302N). The organic-inorganic composite sponge-like porous diaphragm was loaded in the middle of an H-type electrolytic cell. The test environment temperature was 25 °C, the electrolyte was a 30 wt% KOH solution, and the frequency range of the impedance test was set to 1×10 -1 Hz~1×10 5 Hz, the amplitude was set to 10mV, and each organic-inorganic composite sponge-like porous membrane sample was tested in parallel 3 times, and the average value was taken. The membrane surface resistance (Ω·cm 2 ) is calculated as follows:
[0106] AR=(Z′-Z′ 0 )·A
[0107] Among them, Z' represents the real impedance value of high frequency in the film state (Ω), Z' 0 represents the real impedance value of high frequency without membrane (Ω), and A represents the effective area of the diaphragm (1.766cm 2 ).
[0108] b. Application: The organic-inorganic composite sponge-like porous diaphragm prepared in Example 1, the organic-inorganic composite finger-shaped porous diaphragm prepared in Comparative Example 1, and commercial diaphragms 1 to 4 are respectively assembled with nickel-plated stainless steel bipolar plates with direct current, cathode Raney nickel mesh, anode pure nickel mesh, and polytetrafluoroethylene sealing gaskets to form an electrolytic cell, and the assembly pressure is 2MPa. The alkaline electrolysis performance of water is tested using a direct current power supply, the electrolyte is a 30wt% KOH solution, the temperature is 80°C, and the organic-inorganic composite sponge-like porous diaphragm prepared in Example 1, the organic-inorganic composite finger-shaped porous diaphragm prepared in Comparative Example 1, and commercial diaphragms 1 to 4 are measured at a current density of 0.4A / cm 2 ~1.0A / cm 2 The water electrolysis voltage under the range is shown in Table 1.
[0109] Table 1 Voltage test results of the prepared organic-inorganic composite sponge-like porous diaphragm, the organic-inorganic composite finger-like porous diaphragm prepared in Comparative Example 1, and commercial diaphragms 1 to 4
[0110]
[0111] Observation of Table 1 shows that the organic-inorganic composite sponge-like porous diaphragm of Example 1 exhibits the lowest water electrolysis voltage. This shows that the organic-inorganic composite sponge-like porous diaphragm prepared in Example 1 is superior to other tests in promoting the ionization of water molecules, improving ion conduction efficiency and reducing energy consumption; in contrast, the organic-inorganic composite finger-shaped porous diaphragm of Comparative Example 1 exhibits the highest water electrolysis voltage at all current densities. This means that the organic-inorganic composite finger-shaped porous diaphragm in Comparative Example 1 causes a large energy loss during the electrolysis process, thereby requiring a higher voltage to maintain the same current density.
[0112] Figure 1 This is a cross-sectional electron microscope image of the organic-inorganic composite sponge-like porous diaphragm prepared in Example 1. Figure 2 It was concluded that the organic-inorganic composite finger-shaped porous diaphragm has sponge-like pores inside that are interconnected, have a high porosity, and have a thinner non-microporous layer at the top.
[0113] Figure 2This is a cross-sectional electron microscope image of the organic-inorganic composite finger-shaped porous diaphragm prepared in Comparative Example 1. Figure 1 It was concluded that the organic-inorganic composite finger-shaped porous diaphragm has finger-shaped pores inside, the pores are not connected, the porosity is low, and there is a thicker non-microporous layer on the top.
[0114] Figure 2 and Figure 1 The comparison results show that if only porogen is used, a porous structure can be provided, but the pores are not connected; however, if the porogen is used and then a pre-phase conversion treatment is performed, sponge-like pores that are interconnected are obtained, which overcomes the technical defects of the prior art organic-inorganic composite porous membrane, that is, the pore structure is not connected, dead zones are easily formed, and ion conduction is affected.
[0115] Figure 3 The ionic impedance diagrams of the organic-inorganic sponge-like porous membrane prepared in Example 1, the organic-inorganic finger-like porous membrane prepared in Comparative Example 1, the carbon membrane, the carbon energy membrane, the carbon harmonic membrane and the Cobetter membrane are calculated based on the results of the electrochemical impedance spectroscopy. Figure 3 It is concluded that the organic-inorganic composite sponge-like porous membrane prepared in Example 1 has a lower impedance value than the commercial membrane, while the organic-inorganic composite finger-like porous membrane prepared in Comparative Example 1 has a higher impedance. The comparison results show that the non-connected porous structure membrane prepared only with the porogen has ion conductivity; and after the porogen is used and then the pre-phase conversion treatment is performed, the sponge-like pores that are interconnected are obtained, and the ion conductivity is greatly improved, which overcomes the technical defect of the prior art that the ion conduction channels of the organic-inorganic composite porous membrane are not connected, resulting in a higher impedance.
[0116] Figure 4 The water contact angle data of the organic-inorganic sponge-like porous membrane prepared in Example 1, the organic-inorganic finger-like porous membrane prepared in Comparative Example 1, the carbon membrane, the carbon energy membrane, the carbon harmonic membrane and the Cobetter membrane are shown in FIG. Figure 4 It was found that the water contact angles of the organic-inorganic composite sponge-like porous membrane prepared in Example 1 and the organic-inorganic composite finger-like porous membrane prepared in Comparative Example 1 were both stable at about 40°, which is significantly lower than the water contact angles of commercial membranes 1 to 4, indicating that the introduction of metal oxide nanoparticles can significantly improve the hydrophilicity of the membrane, overcoming the technical defect of poor hydrophilicity caused by the highly hydrophobic structure of the polyarylether polymer material in the organic-inorganic finger-like porous membrane.
[0117] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an organic-inorganic composite sponge-like porous diaphragm, characterized in that: The following steps are involved: The polyarylether polymer material, the porogen, the metal oxide nanoparticles and the organic solvent are mixed, and then defoamed to obtain a casting liquid, and the casting liquid is made into a liquid film; In the casting solution, the mass percentage of the polyarylether polymer material is 5% to 20%, the mass percentage of the porogen is 0.5% to 5%, the mass percentage of the metal oxide nanoparticles is 0.5% to 10%, and the organic solvent is supplemented to 100%; The polyarylether polymer material is selected from polyarylether polymers or sulfonated derivatives of polyarylether polymers; The liquid film is placed in a humid air atmosphere for pre-phase conversion. During the pre-phase conversion, water vapor in the humid air partially penetrates into the liquid film and undergoes a preliminary exchange with the organic solvent in the liquid film, inducing the formation of a through sponge-like porous structure inside the liquid film, thereby obtaining a sponge-like porous liquid film. Subsequently, the sponge-like porous liquid membrane is placed in an extractant for phase transformation. During the phase transformation, the membrane pores of the sponge-like porous liquid membrane condense, and at the same time, the polyarylether polymer material is enriched to form a continuous phase and solidified into a film, thereby obtaining an organic-inorganic composite sponge-like porous diaphragm.
2. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The thickness of the liquid film is 100 μm to 1000 μm.
3. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The conditions for the pre-phase conversion are: exposing the liquid film to a humid air atmosphere with a relative humidity of 30% to 80% for 1 minute to 30 minutes.
4. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The phase inversion condition is: placing the sponge-like porous liquid membrane in the extractant, soaking it at 0°C to 80°C for 2h to 48h.
5. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The polyarylether polymer material is selected from polyethersulfone, sulfonated polyethersulfone, polysulfone, sulfonated polysulfone, polyetheretherketone or sulfonated polyetheretherketone.
6. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The porogen is selected from di-n-butyl phthalate, polyethylene glycol or polyvinyl pyrrolidone.
7. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 1, characterized in that: The metal oxide nanoparticles are selected from one or more of ZrO2, TiO2, Al2O3, SiO2, CeO2, MnO2, and Fe3O4.
8. The method for preparing the organic-inorganic composite sponge-like porous diaphragm according to claim 7, characterized in that: The particle size of the metal oxide nanoparticles is 5nm to 500nm.
9. An organic-inorganic composite sponge-like porous diaphragm prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the organic-inorganic composite sponge-like porous diaphragm according to claim 9 in preparing a diaphragm for electrolysis of alkaline water.
Citation Information
Cited By
Organic / inorganic composite porous heat insulation film and preparation method thereof
CN119684668A
Organic blending type porous diaphragm as well as preparation method and application thereof
CN121137687A
Alkaline electrolyzed water porous diaphragm as well as preparation method and application thereof
CN121137688A
Porous composite organic-inorganic diaphragm, preparation method of porous composite organic-inorganic diaphragm, electrolytic hydrogen production device and application of porous composite organic-inorganic diaphragm
CN121204736A